Jigsaw Method in Increasing Students’ Interest in English Language Learning at MA Al-Khoirot - Ula Na’matul Afifah; Mulis Mulis (Pusat riset dan Inovasi Nasional, 2025)
Low student interest in learning English remains a challenge in many Islamic senior high schools, particularly in rural areas where teacher-centered instruction is still dominant. One strategy proposed to address this issue is the Jigsaw method, a cooperative learning approach that emphasizes student collaboration, responsibility,p and peer teaching. This classroom action research was conducted at Madrasah Aliyah Al-Khoirot to examine the effectiveness of the Jigsaw method in increasing students’ interest in learning English, specifically in descriptive text material. The participants consisted of 31 eleventh-grade students, and the study was implemented in two cycles following the Kemmis and McTaggart model. Data were collected through observation, questionnaires, interviews, and tests. The findings showed that the Jigsaw method significantly improved student engagement and learning outcomes. The percentage of students who achieved the minimum passing grade (KKM) increased from 35.48% in the pre-cycle to 77.42% in the second cycle. Additionally, 86.4% of students responded positively to the use of the Jigsaw method, citing increased motivation, understanding, and cooperation. Observation results also revealed active participation, especially in peer explanation and group discussions. Based on these findings, the Jigsaw method is considered effective in fostering student interest, promoting active learning, and creating a more interactive classroom environment. It is therefore recommended as an alternative strategy to enhance English learning motivation in Islamic senior high school settings.